Collocations in CALL: an investigation of vocabulary-building software for EFL - Nesselhauf, Nadja; Tschichold, Cornelia (Computer assisted language learning, 2002)
In this paper, CALL software for English vocabulary-learning is tested as to its usefulness for learning collocations. Our analysis of seven commercially available programs - most of them for German-speaking learners - shows that, so far, collocations have been largely neglected in CALL. A number of suggestions are made for collocational exercises that are likely to be both useful for the learner and easy to implement in a CALL program.